Sustainable Cities in the Netherlands: Urban Green Spaces Management in Rotterdam - Choerunisa Noor Syahid; Ayu Nova Lissandhi; Kurnia Novianti; Abdul Fikri Angga Reksa (Journal of Indonesian Social Sciences and Humanities, 2017)
One of the challenges of sustainable urban development is to provide a viable environment for the population following the function of space and community activities within it. Research on green space in the Netherlands is important as a response to the global environmental crisis as well as the realization of sustainable development. This research uses an interdisciplinary approach through the analysis of the phenomena of spatial management in the context of local-global sustainable urban development. An interdisciplinary approach is used because the issue of "sustainable cities" is multidimensional, so it takes more than one perspective in reviewing it, in this multidisciplinary research involved among other anthropology, urban social planning, and sociology. Based on the research problem formulated, the science perspectives are expected to answer the question of how space is interpreted, negotiated and become a vehicle for the distribution of sustainable development ideas. This dynamic also captures the context of green space management so that this study contributes to enriching theoretical studies on the construction of urban spaces. This research question is answered through qualitative methods of collecting primary data through interviews, focused discussions and observations, as well as searching related literature as secondary data. The result of this study found that the attention of the Dutch environmental policy has also regulated spatial management, primarily related to "space" as part of human activities and has environmental and social impacts. Spatial policy in the Dutch context is articulated as a place of negotiation embodied in the EU's global and regional collective consensus.